A panacea for development? Megaprojects and the construction of state legitimacy in post-apartheid South Africa. Issue 3 (3rd July 2019) - Reboredo, Ricardo
ABSTRACT: Megaprojects have proven to be indispensable politico-economic instruments for South Africa throughout its post-apartheid period and have been presented as singular solutions for the country's enduring problems of poverty and inequality. This paper will analyze the roles and rationales of South African megaprojects and argues that they have been among the main instruments used by the state to construct its authority. Additionally, the paper contends that given the country's faltering post-apartheid economic trajectory and state-oriented developmental vision, specific sectors including energy, housing, and manufacturing have become dependent on state-led megaproject-based initiatives.